Exploratory Analysis of Physical Therapy Process of Care and Psychosocial Impact of the COVID-19 Pandemic on Physical Therapists. Issue 6 (5th March 2021) - Tiwari, Devashish; Naidoo, Keshrie; Chatiwala, Naseem; Bartlo, Pamela L; Triola, Allison; Ong, Brandon; Gore, Shweta
Abstract: Objective: The purpose of this study was to investigate the physical therapy process of care, clinical practices, and the self-reported psychosocial impact of working during the 2020 pandemic on physical therapists and physical therapist assistants. Methods: An electronic survey including closed and open-ended questions was distributed to physical therapists employed in a range of health care settings across the United States. Results: Physical therapy use and process of care varied across settings. Feasibility of performing an assessment was the main driver for selection of outcome measures. Interventions were mainly geared toward improving respiratory function and deconditioning. Prone patient positioning, now commonplace, was used infrequently by therapists in acute care prior to coronavirus disease 2019 (COVID-19). Similarly, outpatient and home care settings noted an increase in the use of respiratory-driven interventions such as incentive spirometry and breathing exercises. Qualitative data analysis revealed both physical barriers (personal protective equipment [PPE]) and social barriers to care. Therapists noted challenges in discharge planning and patient/family education due to the impact of social isolation. They also noted difficulty maintaining productivity standards because of additional time spent in changing PPE and following safety measures. Participants dealt with rapid changes in their role, changing productivity standards, and needing to increase their knowledge in a short amount of time. Conclusion: Physical therapy use varied widely across settings. Despite some concern for personal health, respondents felt that the COVID-19 pandemic increased a sense of togetherness among team members and promoted greater appreciation for life and work. Impact: This exploration of the process of care and current clinical practices across settings provides important knowledge about the role of physical therapists and physical therapist assistants in the care of patients with COVID-19. Gaining an understanding of the psychosocial impact of the pandemic among therapists could assist in creating solutions to better support clinicians' well-being.